The Reimagining of Place in English Modernism. - Wiseman, Sam (Liverpool University Press, 2015)
Analyses key texts by D.H. Lawrence, John Cowper Powys, Mary Butts and Virginia Woolf, charting their respective attempts to forge new identities, perspectives and literary approaches that reconcile tradition and modernity, belonging and exploration, the rural and the metropolitan.